CO2 (Carbon Dioxide) Metric Monitoring Tool Based on Internet of Things (IoT) - Iwan Pahendra; Eva Damila; Ermatita (Jurnal Mantik, 2020)
Monitoring of CO2 (Carbon Dioxide) metric on campus is very necessary to do. A lot of vehicles passing by on campus will make pollution bigger day by day. Development of green campus has to be done at this time. Based on UI Green Metric 2018, 719 campuses have participated to develop a green campus and issues of sustainability. One of requirement is implementation of smart system to solve pollution problems. To develop CO2 metric monitoring tool based on IoT needs hardware and software. The hardware consists of CO2 sensor type MG-811, communication module SIM 800, ADC module ADS1115 and microcontroller ESP32. Software is done using PHP and database. Parameters to be measured is CO2 level. Furthermore, information about CO2 level can be displayed and accessed in real-time via computers. The sensors read the value every in 5 seconds. The results is in average value, CO2 level is 25.50 ppm (parts per million). There is below threshold value for CO2 level according to government regulation. It is a normal condition and no pollution because campus is still in lockdown.